Shared and divergent patterns in narrative skills: comparing English monolingual and Japanese–English bilingual children - Hayes, Richy Lewis; Kan, Pui Fong (Frontiers in Psychology, 2026)
Narrative production requires coordinating lexical, grammatical, and discourse skills. For bilingual children, these abilities develop across two languages, influencing how resources are used during storytelling. This study compared Japanese–English bilingual and English monolingual children’s narrative microstructure and macrostructure. Twenty-eight children in each group (ages 3–8, matched for age and sex) completed the English version of the Multilingual Assessment Instrument for Narratives (MAIN). Measures included mean length of utterance in morphemes (MLUm), number of different words (NDW), subordination index (SI), fragments, story structure (SS), structural complexity (SC), internal state terms (IST), and comprehension, as well as which MAIN episode was told with the most complexity. All micro- and macrostructure measures increased with age except SC. Group differences appeared only in NDW. Age × group interactions for MLUm, SI, and NDW showed bilingual preschoolers had the lowest scores, while bilingual school-age children produced the most fragments. Age and language groups did not differ in which episode they told most complexly: all participants produced the most complex retellings for episode one and the least for episode two. Overall, microstructure was more sensitive to language experience, whereas macrostructure remained relatively stable across groups. Older children outperformed younger children, and episodic complexity patterns were consistent across age and language.